A new glycosidic antioxidant from Ranunculus muricatus L. (Ranunculaceae) exhibited lipoxygenasae and xanthine oxidase inhibition properties. Issue 11 (3rd June 2017) - Raziq, Naila; Saeed, Muhammad; Ali, Muhammad Shaiq; Zafar, Salman; Shahid, Muhammad; Lateef, Mehreen
Abstract: Phytochemical investigation of Ranunculus muricatus L. (Ranunculaceae) led to the isolation of a new metabolite named as ranuncoside from the ethyl acetate fraction of the plant. Structure of the novel compound was elucidated through detailed spectroscopic analyses, using UV, IR, 1 H, 13 C NMR and 2D NMR in combination with EIMS and HR EI-MS techniques. The compound was evaluated for antioxidant activity using the 1, 1-diphenyl-2-picryl-hydrazyl (DPPH) free radical scavenging assay. Its inhibitory potential was tested against lipoxygenase and xanthine oxidase enzymes. Ranuncoside potently scavenged the DPPH free radicals (IC50  = 56.7 ± 0.43 μM) and strongly inhibited the activities of lipoxygenase (IC50  = 63.9 ± 0.17 μM) and xanthine oxidase (IC50  = 43.3 ± 0.22 μM). Abstract :